Farrowing duration and its effects on pig performance - Wheat, J.D.; Allee, G.L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Based on the first 76 farrowings recorded, average duration (the time between the birth of the first pig and of the last pig in the litter) was 129.09±7.28 minutes, and the average time interval between pigs was 15.71± 1.02 minutes. Longer farrowings were associated with longer intervals (r=.73), but farrowing duration and litter size at birth were not closely related (r=.19, P>.05). Farrowing duration was positively associated with the number of pigs born alive (r=.34, P<.0l). Farrowing interval, a better criterion of speed of farrowing than farrowing duration, was significantly associated with number of pigs alive at birth and at weaning; the correlations were, respectively, -.75 and -.78. Farrowing interval was also negatively associated with litter weight at 21 days, the correlation was -.32 (P<.05). So naturally it was negatively associated with the National Swine Improvement Federation's sow-productivity index: (r=-18, P<.05). The index is 6.5 times the number of pigs born alive plus litter weight of pigs 21 days old. The number of live pigs per litter at birth averaged 9.75±.34 and at 21 days, 8.60±1.2.
Keywords: Swine; Farrowing; Pig performance